Umetnost improvizacije v literaturi in glasbi - Dović, Marijan (Primerjalna književnost, 2015)
The article deals with the art of improvisation in literature and music. With reference to two highly elaborate contemporary forms of improvisation - poetry of Basque bertsolaris and jazz - it explores the possibilities for comparing the improvisational practices within the two artistic disciplines.
Keywords: jazz; književnost in glasba; bertsolaritza; improvizacija; ljudsko pesništvo; baskovska književnost